Effects of adjunctive pimavanserin and current antipsychotic treatment on QT interval prolongation in patients with schizophrenia - Bugarski-Kirola, Dragana; Nunez, Rene; Odetalla, Ramzey; Liu, I-Yuan; Turner, Mary Ellen (Frontiers in Psychiatry, 2022)
Background: Pimavanserin prolongs the QT interval, with mean increases in corrected QT (QTc) of 5–8 ms, and is currently being investigated for the treatment of negative symptoms of schizophrenia. Objectives: To assess QT interval prolongation in 3 studies investigating once-daily pimavanserin as an adjunct to current antipsychotic treatment in patients with schizophrenia. Methods: Electrocardiograms were unblinded from trials in which pimavanserin or placebo was added to main antipsychotics over 6 weeks (ENHANCE), 26 weeks (ADVANCE), and up to 78 weeks (ongoing 52-week, open-label extension study [study 035]) of treatment. Antipsychotic treatment was permitted throughout these studies. The 3 most frequently used antipsychotic treatments were examined—aripiprazole (including long-acting injectable), risperidone (including long-acting injectable), and olanzapine. QT intervals were corrected (QTc) using Fridericia's method, with elevated risk defined as either postbaseline value maximum of >500 ms or change from baseline to postbaseline maximum of >60 ms. Results: Of patients treated with adjunctive pimavanserin in ENHANCE, there were no postbaseline QTc values >481 ms; one patient in each of the risperidone and aripiprazole groups had change from baseline to postbaseline maximum >60 ms. More patients had change from baseline to postbaseline maximum ranging from 31–60 ms in the risperidone plus adjunctive placebo group (n = 5; 6.6%) than those in the risperidone plus adjunctive pimavanserin group (n = 3, 4.1%). In the pimavanserin plus antipsychotic group of ADVANCE, one patient had postbaseline QTc value >481 ms, and one patient treated with aripiprazole had change from baseline to postbaseline maximum of >60 ms. In study 035, a change from double-blind baseline to overall postbaseline maximum >60 ms occurred in one patient treated with aripiprazole and pimavanserin and in one patient treated with risperidone and pimavanserin. Similar proportions of patients had changes from double-blind baseline to post double-blind baseline maximum between 31–60 ms across treatments. No adverse events associated with an increase in the QTc interval were reported. Conclusions: Adjunctive pimavanserin with background antipsychotic treatment showed no evidence of QTc prolongation >500 ms postbaseline, consistent with previously reports on QT prolongation with pimavanserin.